Understanding the Force of Law - Tyler, Tom R (2015)
The Force of Law raises a fundamental question: what is the nature of the force underlying legal authority? Frederick Schauer does an excellent job describing the history of two models of the nature of that force: coercion (i.e., sanction based) and sanction-independent. Having identified these two distinct models, he then tries to make the case that the law is primarily about coercion and that the role of sanction-independent force has been overstated